Heat transduction in rat sensory neurons by calcium-dependent activation of a cation channel - Reichling, David B. (The National Academy of Sciences of the USA, 1997)
The mechanism of heat transduction in vertebrate sensory neurons was investigated in vitro by using cultured dorsal root ganglion neurons from adult rat. In response to a physiologically relevant range of stimulus temperatures (23–45°C), a subpopulation of small dorsal root ganglion neurons are depolarized by a cation current (heat-activated current, I(heat)) that is antagonized by extracellular cesium. Heat-induced single-channel currents in cell-attached patches are evoked at a similar range of temperatures. I(heat) is a calcium-dependent current activated indirectly by heat-evoked release of calcium from intracellular stores. This suggests that the channel itself is not the transducer of thermal energy. Similar to nociceptive heat sensation in vivo, I(heat) is enhanced by the hyperalgesic agent prostaglandin E(2) and only partially adapts during prolonged heat stimuli. To our knowledge, these data provide the first demonstration that ion channels can mediate heat transduction in mammalian sensory neurons and provide evidence that heat causes the channels to open via an increase in the intracellular second messenger calcium.